1994
DOI: 10.1104/pp.105.1.225
|View full text |Cite
|
Sign up to set email alerts
|

Peach (Prunus persica) Endopolygalacturonase cDNA Isolation and mRNA Analysis in Melting and Nonmelting Peach Cultivars

Abstract: Two distinct partial cDNAs, PRFl and PRF3, similar in sequence to previously described polygalacturonases, were amplified from ripe peach (Prunus persica 1. Batsch cv Flavorcrest) fruit cDNA by the polymerase chain reaction. PRF1-related RNA was present in fruit from early ripening at levels not detected by northern analysis. PRF3-related RNA was readily detectable in ripe fruit by northern analysis. PRF3 was used to isolate a cDNA with a complete open reading frame, PRFS, from a XZAP li cDNA library prepared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
71
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 23 publications
5
71
0
1
Order By: Relevance
“…The TAPG gene products from tomato most likely encode endopolygalacturonases due to their high percent identity with the PFPG (62% identity), which was shown to encode an endopolygalacturonase (Lester et al, 1994). Moreover, in the dendrogram shown in Figure 3 the fruit and abscission PGs are grouped separately from the pollen PGs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The TAPG gene products from tomato most likely encode endopolygalacturonases due to their high percent identity with the PFPG (62% identity), which was shown to encode an endopolygalacturonase (Lester et al, 1994). Moreover, in the dendrogram shown in Figure 3 the fruit and abscission PGs are grouped separately from the pollen PGs.…”
Section: Discussionmentioning
confidence: 99%
“…The TAPG2 cDNA includes an approximately 150-bp poly(A) tail at the 3' end. The first 18 amino acids of the deduced amino acid sequence includes a hydrophobic core of amino acids and a cleavage site indicative of a signal peptide (von Heijne, 1983 (Delia Penna et al, 1986), and PFPC (Lester et al, 1994) Percent identities for the alignments of peptide sequences are shown in boldface. signal peptide) has a predicted molecular mass of 40.1 kD, identical to that of the TAPG1 peptide, and a pi of 8.08.…”
Section: G a A G A A C T T A G T A M T G C T T A T A A A T T A T A C mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, endopolygalacturonase (endo-PG, EC 3.2.1.15) is an enzyme involved in the depolymerization of pectin, a major component of cell walls that is extensively disassembled during the late stages of fruit softening (Hayama et al, 2003(Hayama et al, , 2006aTatsuki et al, 2013). On this same note, the lack of a melting phase in nonmelting flesh (NMF) genotypes has been shown to be caused by a deletion of the endo-PG genes or a truncation of their mRNAs, which, in turn, causes an absence of the immunodetectable endo-PG protein (Lester et al, 1994;Brummell et al, 2004). These data indicate that endo-PG-mediated pectin modification may play an important role in the later stages of softening and textural changes during the ripening of the peach.…”
Section: Introductionmentioning
confidence: 99%
“…At present, published studies have mainly focused on analyzing the activities and gene expression of endo-PG (Lester et al, 1994;Ma et al, 1999;Hayama et al, 2003;Brummell et al, 2004;Tatsuki et al, 2013); only a few studies have yet to analyze SNPs (Hayama et al, 2006a). In one of these studies, the selected fragments of an endo-PG gene (1172 bp) from the genomic DNA isolated from 2 peach cultivars were subsequently amplified, cloned, and sequenced, showing 31 SNPs, 2 main deletions of 17 bp each, a 2-bp deletion, and a 2-bp insertion (Morgutti et al, 2006).…”
Section: Introductionmentioning
confidence: 99%